An Infant With Transient Neonatal Pustular Melanosis Presenting as Pustules - Pei-San Chia; Cheung Leung; Yu-Ling Hsu; Cheng-Yu Lo (Pediatrics and Neonatology)
Transient neonatal pustular melanosis is mostly found in full-term black infants. It is a benign and self-limited disease, and the etiology is still unknown. We present a full-term female neonate with multiple vesiculopustular and pigmented macular lesions found immediately after her birth. A skin biopsy showed vesicles consisting of intracorneal and subcorneal aggregates of neutrophils, which is compatible with transient neonatal pustular melanosis. Although it is rare in Taiwan and Asian countries, transient neonatal pustular melanosis should always be considered when pustulosis is found in the neonatal period to prevent the use of unnecessary antibiotics. Dermatological consultation and histological confirmation are sometimes required for the final diagnosis.